Odpowiedzi

Najlepsza Odpowiedź!
2010-01-27T14:47:07+01:00
1. 2(-3a-4b)-3(a+2b)+4(2a+3b)=(-6a-8b)-(3a+6b)+(8a+12b)=-6a-8b-3a-6b+8a+12b=-a-2b
a = -3 i b= 2
-(-3)-2*2=3-4=-1
2. 3(3x-1)(4+2x)-4(x+3)(4x-1)=3(12x+6x²-4-2x)-4(4x²-x+12x-3)=
=3(6x²+10x-4)-4(4x²+11x-3)=18x²+30x-12-16x²-44x+12=
=2x²-14x
x=2½=⁵/₂
2x²-14x=2*(⁵/₂)²-14*(⁵/₂)=2*(²⁵/₄)-35=²⁵/₂-35=12½ -35=
=-22½
2010-01-27T14:47:45+01:00
1.
2(-3a-4b)-3(a+2b)+4(2a+3b)=-6a-8b-3a-6b+8a+12b=-a-2b
a=-3, b=2
-a-2b=-(-3)-2*2=6-4=2
2.
3(3x-1)(4+2x)-4(x+3)(4x-1)=3(12x+6x²-4-2x)-4(4x²-x+12x-3)=
=3(6x²+10x-4)-4(4x²+11x-3)=18x²+30x-12-16x²-44x+12=
=2x²-14x
x=5/2
2x²-14x=2*(5/2)²-14*(5/2)=2*(25/4)-35=25/2-35=12 i 1/2 -35=
=-22 i 1/2